Fifty Years of the American Finance Association - KEENAN, MICHAEL (Journal of Finance, 1991)
ABSTRACT The American Finance Association was organized 50 years ago. This paper reflects on recent trends in Officers and Directors, Membership, Association Meetings, the Journal of Finance , and other activities. Appendix Tables provide historical data for the Association for the past 25 years.